A Novel Label-Free Optical Biosensor Using Synthetic Oligonucleotides from E. coli O157:H7: Elementary Sensitivity Tests - Bahsi, Zehra Banu; Bueyukaksoy, Aliguel; Olmezcan, Sinan Mert; Simsek, Fethi; Aslan, Muhammed Hasan; Oral, Ahmet Yavuz (Mdpi, 2009)
SiO2-TiO2 thin films for use as fiber optic guiding layers of optical DNA biosensors were fabricated by the sol-gel dip coating technique. The chemical structure and the surface morphology of the films were characterized before immobilization. Single probe DNA strands were immobilized on the surface and the porosity of the films before the hybridization process was measured. Refractive index values of the films were measured using a Metricon 2010 prism coupler. On the surface of each film, 12 different spots were taken for measurement and calculation of the mean refractive index values with their standard deviations. The increased refractive index values after the immobilization of single DNA strands indicated that immobilization was successfully achieved. A further refractive index increase after the hybridization with target single DNA strands showed the possibility of detection of the E. coli O157:H7 EDL933 species using strands of 20-mers (5'-TAATATCGGTTGCGGAGGTG-3') sequence.
Keywords: sol-gel; optical DNA biosensor; prism coupler